Hepatitis E Virus in Pigs from Slaughterhouses, United States, 2017–2019 - Sooryanarain, Harini (Emerg Infect Dis, 2020)
Hepatitis E virus (HEV) RNA was detected in 6.3% and HEV IgG in 40% of 5,033 serum samples from market-weight pigs at 25 slaughterhouses in 10 US states. The prevalent HEV genotype was zoonotic genotype 3, group 2. Blood of HEV-viremic pigs from slaughterhouses may contaminate pork supply chains.